Moderation of Regional Original Revenue and Capital Expenditure on Economic Growth - Riyans Ardiansyah; Marten Puyo; Mursalim Salam (Journal of Governance, Taxation and Auditing, 2026)
The purpose of this study is to examine the effect of regional original revenue and capital expenditure on economic growth, with balancing funds as a moderating variable. The study population consisted of regional financial data from five regencies/cities in North Kalimantan Province. The sample selection method used purposive sampling. The data consisted of Gross Regional Domestic Product (GDP) at constant prices to determine economic growth in North Kalimantan regencies/cities, realized regional income (PAD), capital expenditure, and balancing funds. Data analysis methods used descriptive statistical analysis, linear regression, and moderated regression analysis. The results of the study indicate that Regional Original Revenue (PAD) partially has no positive effect on economic growth. Capital Expenditure has a positive and significant effect on economic growth. The Balancing Fund has no direct effect on economic growth. The Balancing Fund is proven to act as a pure moderator in the relationship between Capital Expenditure and Economic Growth. Conversely, the Balancing Fund is unable to moderate the relationship between Regional Original Revenue and Economic Growth. Simultaneously, PAD, Capital Expenditure, and the Balancing Fund are able to explain variations in regional economic growth quite well, although there are still other factors outside the model that also influence economic growth.